Shepherd 's Role In Stewardship Church During the Covid-19 Pandemic - Salmon Ephraim Ngesthi, Yonathan; Ming , David (Riviera Publishing, 2022)
Introduction: church moment this in difficult times for could do all service , result from a pandemic that is still in progress this . Objectives: Shepherd have Fright to pandemic However shepherd is also in the call must keep going serve . Methods: Through method study qualitative descriptive could concluded that shepherd could do with equip and understand about c stewardship according to Bible Results: next in service bring Among connection Church and Stewardship as base in actualize so that bring The duties and roles of the Shepherd Hearing in Stewardship nice church _ this addressed in Stewardship During the COVID-19 Pandemic . Although there is an epidemic problem disease this no can stop shepherd in doing service stewardship church , because church must keep going capable adapt yourself and survive in dependency to God , so church could do various appropriate way _ with rule of the protocol program health the government should obeyed by strict Conclusion: With so could concluded that Shepherd 's Role in stewardship The Church during the Covid-19 Pandemic can conducted with equip and understand about c stewardship according to Bible